Temperature Triggered In situ Gelling System for Betaxolol in Glaucoma - A. Geethalakshmia, Roopa Karkib, Poornima Sagib, Sajal Kumar Jhac, Venkatesh.D.Pb (Journal of Applied Pharmaceutical Science, 2013)
The aim of this research is to develop thermo sensitive drug vehicles for glaucoma therapy in in-situ form to overcome the problems of poor bioavailability, naso lachrymal drainage and rapid precorneal elimination exhibited by conventional eye drops. Thermo sensitive ophthalmic drop was prepared using cold method by mixing thermo sensitive polymer pluronic F-127, viscosifying agent HPMC-E 50 LV and antiglaucoma drug (betaxolol hydrochloride). Prepared in situ gels were evaluated for physical parameters like appearance, gelation temperature, pH, drug content, rheological properties, isotonicity, sterility test, in vitro permeation and in-vivo ocular irritation study. The drug released from selected batch provides sustained release of betaxolol over 7 hours period and showed excellent ocular tolerance. The overall results of this study supports that the Pluronic/HPMC based vehicle could be used for controlled drug release that exhibits a greater potential for glaucoma therapy.
Keywords: Glaucoma, In situ gel, ocular drug delivery, &be